Kajian Literatur: Peran Komitmen Organisasi Pada Kinerja Dan Kepuasan Kerja Karyawan Saat Pandemi Covid-19 - Phaedra, Putra; Astiti, Dewi Puri; Widiasavitri, Putu Nugrahaeni (Jurnal Ilmiah Wahana Pendidikan, 2024)
Company needs to have the competitive capabilities that are the core of company’s failure or success. Maximizing the company’s competitive capability can be done by employee. The presents of Covid-19 is giving impact to company and made company needs to put some efforts to maintain the company’s businesses. One of the efforts is corresponded with the decreased of employee’s remuneration. Companies need employee’s loyalty to stay in work for maintaining the company’s businesses. Employee’s loyalty also can be called as organizational commitment. There are lot of studies about organizational commitment toward employee before the Covid-19’s pandemic, therefore recent information about organizational commitment toward employee is needed especially work performance and satisfaction on employee during Covid-19’s pandemic. This literature review examines the importance of organizational commitment toward work performance and satisfaction on employee in a company during Covid-19’s pandemic. The conclusion is organizational commitment still affects employee’s work performance and work satisfaction although not all studies show organizational commitment affects it independently during Covid-19’s pandemic.